2015
DOI: 10.4314/gmj.v49i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the cardiothoracic ratio using chest radiographs in an indigenous Ghanaian population: a simple tool for cardiomegaly screening

Abstract: SUMMARYBackground: Cardiothoracic ratio is a simple and cheap tool in the estimation of heart size. It is a useful index of cardiac size evaluation, and a value of 50% is generally considered to indicate the upper limit of normal. Study Objective: This study is to ascertain the normal mean value in cardiothoracic ratio of Ghanaians using chest radiography to serve as baseline for screening for cardiomegaly. Methodology: Standard postero-anterior radiographs of the -clients/patients were used in the study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 10 publications
5
29
1
Order By: Relevance
“…The average CTR differed for different genders and age groups. Previous studies have shown that CTR was higher in females than in males (Brakohiapa et al, 2017;Mensah et al, 2015). In contrast, our results revealed that CTR was higher in males than in females.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…The average CTR differed for different genders and age groups. Previous studies have shown that CTR was higher in females than in males (Brakohiapa et al, 2017;Mensah et al, 2015). In contrast, our results revealed that CTR was higher in males than in females.…”
Section: Discussioncontrasting
confidence: 98%
“…In line with previous studies (Brakohiapa et al, 2017;Mensah et al, 2015), there was a significant correlation between age and CTR in all the patients. The highest value was found in the middle-aged group (37-58 years).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations